An Observational Study to Assess the Level of Awareness and Perception of Toxoplasmosis among women of Childbearing age in Gaza City, Palestine - Zuhair Dardona, Adnan Al Hindi, Mohamed Hafidi, Ali Boumezzough, Fadel A. Sharif, Samia Boussaa (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Toxoplasmosis is one of the world’s most ubiquitous parasitic infections. According to numerous published studies and data, this disease affects approximately one-third of the world’s population. In addition, it is caused by the obligatory intracellular parasite, Toxoplasma gondii. Aim: To assess the level of toxoplasmosis awareness and knowledge among women of childbearing age in Gaza City, Palestine, as well as determine potential risk factors for toxoplasmosis. It is worth emphasizing that the researched region, Gaza City, is one of the world’s most densely populated cities. Method: The study’s assessment approach involved the distribution of 400 questionnaires to women of childbearing age. Aside from gender and age, no other criteria were considered for assessment purposes. Results: The findings of this questionnaire revealed that 38.25% of respondents had heard of this disease, 47.00% were knowledgeable about the means of transmission, and 35.00% were aware of the measures for managing and preventing toxoplasmosis. The most shocking finding was that merely 21.50% of respondents received counseling or information about this ailment, either through educational stages or from their treating physician. Additionally, the findings revealed that consuming raw meat, rearing domestic cats, direct contact with stray cats, and soil are all-important potential risk factors for acquiring this disease. Conclusion: As a result, the study attempted to shed light on the inadequacy of toxoplasmosis knowledge and awareness, particularly among women of childbearing age in the study region. Considering this, the study recommends additional efforts to raise and develop a strong standard for toxoplasmosis knowledge and awareness among women of childbearing age in the study area. Key words: Toxoplasmosis – childbearing age – awareness – risk factors – Gaza, Palestine.